Effects of Digital Health Literacy Program on Sufficient Health Behavior Among Thai Working-Age People With Risk Factors for Noncommunicable Diseases - Ungsinun Intarakamhang; Khwanying Sriprasertpap; Araya Chiangkhong; Niwat Srisawasdi; Supitcha Wongchan; Piya Boocha (SLACK Incorporated, 2024)
Background: Noncommunicable diseases (NCDs) account for more than 75% of deaths in Thailand, which is higher than the global average of 71%. Objective: The aim of this study was to investigate the effects of the Digital Health Literacy (DHL) and Sufficient Health Behavior (SHB) Program on Thai working-age adults age 20 to 65 years with risk factors for NCDs (i.e., overweight and lacking physical activity), and compare the health literacy (HL) and SHB of participants living in urban and semi-urban areas at posttest. Methods: Using the lottery method, this one-group pretest-posttest quasi-experimental design randomly selected 200 participants and assigned them to two equally sized groups. The data were gathered through surveys with an item discrimination power between .20 and .86 and a reliability of 0.94 and were statistically analyzed using t-test and F-test. Key Results: The DHL and SHB Program comprises six sessions over a 12-week period, and activities designed to enhance knowledge of NCDs, HL, health communication, and health behavior modification. It was conducted by health care workers from urban and semi-urban public hospitals via Zoom using various digital toolkits such as YouTube, animations, infographics, role-play videos, clips, and e-books. At the posttest, the participants had higher HL (t = 2.67, p = .001) and SHB (t = 3.36, p = .001). There was a difference in SHB scores (F = 4.640, p = .032) between those living in urban and those in semi-urban areas, but no difference in HL scores (F = 1.436, p = .232). Conclusions: The DHL and SHB Program improved HL and SHB in Thai working-age adults with risk factors for NCDs in both urban and semi-urban communities. [HLRP: Health Literacy Research and Practice. 2024;8(2):e93-e101.]